PERANCANGAN SISTEM INFORMASI PERSEDIAAN ALAT PADA PT ORNAMEN INTI MAKMUR DEPOK - Ibnu Fajar Al Had; Dinda Ayu Muthia; Hanafi Eko Darono (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
Inventory is an asset of an organization that needs to be managed properly so that the operational activities of an organization can run well too. Activities in inventory processing data are mostly carried out by recording item data and providing identity of existing items. The research was conducted at PT Ornament Inti Makmur Depok, the inventory data collection procedure was still not computerized so there were still many obstacles such as data collection of goods that were not recorded properly and also the increasing number of tools which increased every year, the total data on available items was nearly three hundred items for At the moment. Based on the problems mentioned above, a computerized inventory information system is proposed to obtain optimal results so that there are no errors in inventory data collection.